Momento federalista: projetos políticos no alvorecer do Império brasileiro - Oliveira, Leonardo Grão Velloso Damato (2013)
Nine years after obtaining independence from Portugal, the Empire of Brazil spent another nine without a monarch withholding the power. Situated historically between the years of 1831, after D. Pedro I abandoning the throne, and the adulthood of D. Pedro II by 1840, the time of these nine years was called Regency, a moment when the monarch could not obtain the power because of his premature age and when Brazilian society became responsible for their government. This study investigates the ideals that embedded the political projects of Diogo Antonio Feijó and Evaristo Ferreira da Veiga, two important historical characters in the consolidation of the Imperial Estate of Brazil. Aiming to comprehend the multiple forms of conflicting political discourse in that epoch which historians refer to as republican experience, this study attempted to settle a ideological core of the federalists ideals, starting with ideas produced within the American Revolution context. The works of James Madison, Alexander Hamilton and John Jay were studied in order to understand the possible limits of federalist intellectual context, established from the relationship between the variety of possibilities of constituting an Estate and what they elected, within the discourse, as their opponents. Starting the analysis with the Brazilian’s Empire Constituent Assembly in 1823, this research attempted as well to establish a new interpreting possibility of Feijó’s and Evaristo’s political writings, considering possible resemblances among their core ideals and that which the American federalists defended so eagerly.